A Retrospective Observational Study of Socio- Demographic Causes of Death Due to Hanging in Sir Salimullah Medical College Hospital, Dhaka, Bangladesh (The Journal of Ad-din Women's Medical College, 2025)
Background: Hanging is the most common violent asphyxial death in Bangladesh. It is a form of asphyxia by a ligature material around the neck. When the body is suspended by ligature, the body weight constricts force, and the noose moves against gravity. Objective: To evaluate the profile and sociodemographic characteristics in the cause of death due to hanging.Materials and Method: The Department of Forensic Medicine & Toxicology at the Sir Salimullah Medical College in Bangladesh carried out a two year retrospective investigation of hanging deaths from January 2023 to December 2024. Police inquest findings and post-mortem reports were examined. The current study's objective was to examine the different hanging death profiles and contrast the results with previously published research.Result: Most participants were aged 21-30, and 86 (51.5%) were female. Orna was the top choice 104 (62.3%) for ligatures, then rope 44 (26.3%) and gamcha 13 (7.8%). Neck injuries are observed in most cases;158 (94.6%) cases had a solitary ligature mark, while 2 (1.2%) had a double mark, and 7 (4.2%) had a barely visible one.Conclusion: Suicide through hanging remains one of the critical health problems that cause death; factors that contribute to suicide include poverty, family conflict, mental illness, and unemployment. The government and nongovernmental organizations should work to address this issue by focusing on stress management and providing appropriate mental health education.The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 14-17